1997
DOI: 10.2494/photopolymer.10.123
|View full text |Cite
|
Sign up to set email alerts
|

Surface Effects of Plasma Treatments on Some Biodegradable Polymers.

Abstract: Some biodegradable polymers of as poly(y-lactone) and poly(succinate) were surface-treated by glow discharge plasmas under an appropriate condition, and the effects were investigated with respect to the weight loss, surface morphology change, and bio-degradation. The weight loss rates by oxidative plasmas were in general higher than those for a polyester sheet made of poly (ethylene terephthalate). After glow discharge treatments, the characteristic surface morphology appeared by the observation of scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…Hirotsu and others () treated PLA fabrics with plasma using a low pressure radio frequency (RF) glow discharge (13.56 MHz, 10–50 W) and found that oxygen (O 2 ) plasmas have a more pronounced etching effect than nitrogen plasmas and the fabric lost weight in proportion to the applied discharge power. Pankaj and others () treated commercial coextruded PLA films (NatureWorks ® , 32% crystallinity, 43 μm thickness) with atmospheric dielectric‐barrier discharge plasma at 70 and 80 kV for up to 3.5 min and reported that surface roughness increased with increasing voltage and treatment duration.…”
Section: Introductionmentioning
confidence: 99%
“…Hirotsu and others () treated PLA fabrics with plasma using a low pressure radio frequency (RF) glow discharge (13.56 MHz, 10–50 W) and found that oxygen (O 2 ) plasmas have a more pronounced etching effect than nitrogen plasmas and the fabric lost weight in proportion to the applied discharge power. Pankaj and others () treated commercial coextruded PLA films (NatureWorks ® , 32% crystallinity, 43 μm thickness) with atmospheric dielectric‐barrier discharge plasma at 70 and 80 kV for up to 3.5 min and reported that surface roughness increased with increasing voltage and treatment duration.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have investigated the surface modification of PLA by lowtemperature plasmas, most studies having focused on PLA films. Hirotsu et al [16] treated PLA fabrics with lowpressure radiofrequency (RF) glow discharge in pure oxygen or nitrogen and found that weight loss due to plasma etching which was more pronounced for oxygen plasmas than for nitrogen plasmas. The oxygen low-pressure plasma treatment evaluated here did not alter topography at 0.5 min, while at longer times of 5 min clear etching was produced on the surface, with a regular pattern perpendicular to the fiber axis (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, section 4.1 will be much more extensive than the other sections (4.2 up to 4.4) since the availability of literature on these latter approaches is less pronounced. Hirotsu et al published in 1997 one of the first studies on plasma modification of biodegradable polymers and treated PLA fabrics with a low pressure radio frequent (RF) discharge generated in pure oxygen and nitrogen (Hirotsu et al, 1997). The same group reported in 2002 about an enhancement of the wettability of PLLA sheets and showed a strong decrease in water contact angle from 80° to approximately 55° after 30 seconds of oxygen and helium plasma treatment (Hirotsu et al, 2002).…”
Section: Examples Of Plasma-assisted Surface Modification Of Biodegramentioning
confidence: 98%